Comprehensive model for managing water resources in the Baotou City, Inner Mongolia - Xuehai, He; Xioke, Shen; Jingli, Shao; Jiahua, Wei (Journal of Nepal Geological Society, 2000)
Based on the analysis of water resources and water supply condi1ions of the Baotou City, a multi-objective and comprehensive model for managing water resources is established through the selection of decisive variables, analysis of the balance of water resources demand and supply, and the set-up of the managing districts. The optimal distribution of groundwater is strongly emphasised and a response matrix is used to express the restraint of water level in the model. The model is solved using linear objective programming. The analytical results indicate that the optimised scheme has excellent social, economic, and environmental benefits, and can be used as a reference for the development and planning of the Baotou City.